Interpreting the un-expected: Oral realization and translation. (July 2015) - Moore, Susan; Polge, Olivier
Abstract: The study explores the expression of the unexpected by English adjectives and participles prefixed in un - in The Picture of Dorian Gray . The study compares their oral realizations and translations in connection with the various modes of construction of otherness, which can either be a dual opposition between the expected and effective values, with participles and some adjectives, or a gradient between the two values with adjectives. In the case of dual opposition, ungradable adjectives tend to be translated using positive adjectives and there is clear acoustic prominence on the prefix, as in the case of special focus. "Constructed negation" in translation is illustrated by sans + (aucun) NOUN or the suffix -able, and corresponds to greater duration of the prefix. In other cases, the base is acoustically prominent, but translation techniques vary, although four techniques account for 80% of the entries, even if translator styles differ considerably.